2013
DOI: 10.6061/clinics/2013(01)oa12
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the diagnostic values of circulating microRNAs and cardiac troponin T in patients with acute myocardial infarction

Abstract: OBJECTIVE:Recent studies have shown that circulating microRNAs might be useful, novel biomarkers for the diagnosis of acute myocardial infarction. The aims of this study were to evaluate the expression of cardiac-specific miRNAs (miR-1, -133a, -208b, and -499) in patients with acute myocardial infarction and to compare the diagnostic values of these miRNAs with that of cardiac troponin T.METHODS:Sixty-seven plasma samples obtained from patients with acute myocardial infarction and 32 plasma specimens collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(124 citation statements)
references
References 37 publications
(32 reference statements)
3
116
0
Order By: Relevance
“…In the elderly patients with acute NSTEMI, a study showed that circulating miRNA-499-5p had better accuracy in the diagnosis compared with cTnT (23). In line with the above findings, another recent study demonstrated that plasma level of miRNA-499-5p was increased distinctly in AMI patients, suggesting that circulating miR-499-5p could be used for the evaluation of mortality risk (24).…”
Section: Plasma Level Of Mirna-499 and Ami Diagnosissupporting
confidence: 68%
“…In the elderly patients with acute NSTEMI, a study showed that circulating miRNA-499-5p had better accuracy in the diagnosis compared with cTnT (23). In line with the above findings, another recent study demonstrated that plasma level of miRNA-499-5p was increased distinctly in AMI patients, suggesting that circulating miR-499-5p could be used for the evaluation of mortality risk (24).…”
Section: Plasma Level Of Mirna-499 and Ami Diagnosissupporting
confidence: 68%
“…Li et al concluded that the combination of the aforementioned four miRNAs may be useful but is not superior to cTnT for AMI diagnosis [95]. Surprisingly, miR-208a and miR-499a do not belong to the 20 most enriched miRNAs in the blood of MI-patients, as measured by Meder et al in whole blood-microarrays.…”
Section: Mir-1 and Mir-133mentioning
confidence: 89%
“…Posterior wall MI,LWMI, NSTEMI, a VR MI with percentage of 1.5%, 2.0%, 35.0% and 1.5% respectively. In the study of Singh et al [15] reported that troponin T test was positive in the 100% cases with acute MI. According to AlaHussain Abbase Haider [16], level of CK-MB divided into two groups, group with elevated CK-MB patients 35.7% and group with normal CK-MB patients 64.3%.…”
Section: Discussionmentioning
confidence: 99%